2013
DOI: 10.1186/1471-2334-13-117
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxaemia is common in children with Plasmodium falciparummalaria

Abstract: BackgroundChildren presenting to hospital with recent or current Plasmodium falciparum malaria are at increased the risk of invasive bacterial disease, largely enteric gram-negative organisms (ENGO), which is associated with increased mortality and recurrent morbidity. Although incompletely understood, the most likely source of EGNO is the bowel. We hypothesised that as a result of impaired gut-barrier function endotoxin (lipopolysaccharide), present in the cell-wall of EGNO and in substantial quantities in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…This may precipitate injury and impaired gut barrier function either directly or indirectly through local cytokine production, with the subsequent transfer of endotoxin and/or pathogenic bacteria into the blood stream. We have recently shown that endotoxemia is common in SM (28%) and results in temporary immune paralysis similar to that observed in patients with sepsis and experimentally-induced endotoxemia [63]. We hypothesized that the most likely origin of endotoxin was from the gut.…”
Section: Discussionmentioning
confidence: 87%
“…This may precipitate injury and impaired gut barrier function either directly or indirectly through local cytokine production, with the subsequent transfer of endotoxin and/or pathogenic bacteria into the blood stream. We have recently shown that endotoxemia is common in SM (28%) and results in temporary immune paralysis similar to that observed in patients with sepsis and experimentally-induced endotoxemia [63]. We hypothesized that the most likely origin of endotoxin was from the gut.…”
Section: Discussionmentioning
confidence: 87%
“…Further, our observations of ileal mastocytosis in a non-human primate model suggest that mast cells may be cause-and-effect with GI permeability in human malaria. Antihistamine therapy showed a trend toward reduced GI permeability and bacterial translocation in the mouse, suggesting that other mast cell-derived factors likely contribute to GI permeability to resident microbiota, bacterial pathogens, and perhaps ligands such as lipopolysaccharide or peptidoglycan in malaria (Olupot-Olupot et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the challenge is that young infants are not adequately protected against malaria because of their limited coverage by current preventive strategies, such as seasonal malaria chemoprevention and intermittent preventive treatment during infancy, which are not widely implemented. This inadequate coverage is critical because our findings show that young infants can be affected by malaria and subsequently become anemic, which would also potentially increase their vulnerability to other pathogens ( 32 ). Other interventions, such as the RTS,S/AS01 malaria vaccine, which will soon be registered for use, resulted in modest protection against clinical malaria in this age group and did not have any effect on preventing anemia ( 33 ).…”
Section: Discussionmentioning
confidence: 99%